'If you're wrong for the place you just don't survive': examining the work of early career teachers in context. Issue 4 (19th May 2019) - Stacey, Meghan
ABSTRACT: This article presents evidence from across the segregated secondary school system in NSW, Australia, through the close analysis of three cases of teachers' work in contrasting schooling contexts. Through this comparative approach, the relationship between school context and the work of the early career teacher is foregrounded, troubling views of teaching as reflecting a certain kind of life cycle in which early career teachers in particular are seen to be subject to pressures such as stress and burnout. In contrast, I argue that specificities of context, exacerbated by a market-based policy approach which has driven greater levels of differentiation between schools, have particular consequences for teachers, both in the nature and scale of the challenges with which they are faced. In demonstrating how teachers' work is affected by context, I also speak back against recent, often ill-defined discourses of 'classroom readiness' and 'teacher quality', which emphasise the roles of teachers and teacher educators rather the systems within which they work.